2009
DOI: 10.1186/1748-717x-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of patient setup by surface image registration system in conformal radiotherapy of prostate cancer

Abstract: Background: The reproducibility of patient setup for radiotherapy is based on various methods including external markers, X-rays with planar or computerized image acquisition, and, more recently, surface matching imaging. We analyzed the setup reproducibility of 16 patients affected by prostate cancer who underwent conformal radiotherapy with curative intent by using a surface image registration system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 14 publications
2
45
0
1
Order By: Relevance
“…Surface imaging is capable of providing full 3D monitoring of patient position in near real time. The commercially available AlignRT (VisionRT, London, UK) 3D surface imaging system has shown the abilities to detect submillimeter changes in patient position 10 , 12 , 13 , 14 , 15 , 16 , 17 and to accurately localize breast patients for free breathing 18 , 19 , 20 , 21 and deep inspiration breath‐hold treatments 22 , 23 to better than 5 mm. These works have shown that AlignRT is capable of accurately and reproducibly positioning breast tissue relative to treatment isocenter for initial patient positioning and, prior to beam‐on, for breath‐hold treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Surface imaging is capable of providing full 3D monitoring of patient position in near real time. The commercially available AlignRT (VisionRT, London, UK) 3D surface imaging system has shown the abilities to detect submillimeter changes in patient position 10 , 12 , 13 , 14 , 15 , 16 , 17 and to accurately localize breast patients for free breathing 18 , 19 , 20 , 21 and deep inspiration breath‐hold treatments 22 , 23 to better than 5 mm. These works have shown that AlignRT is capable of accurately and reproducibly positioning breast tissue relative to treatment isocenter for initial patient positioning and, prior to beam‐on, for breath‐hold treatments.…”
Section: Introductionmentioning
confidence: 99%
“…70,71 The system has also been evaluated for respiratory gating in thoracic and abdominal tumor sites and in patient alignment for prostate cancer. 50,72 In such applications, the real-time 3D datasets are matched with corresponding reference images, obtained in the desired respiratory phase at the time of CT simulation. Another published application of this system has been for tracking and aligning the head for high-precision radiosurgery treatment.…”
Section: Ic2 Optical Systems (Alignrt and C-rad Sentinel)mentioning
confidence: 99%
“…While there have been previously published studies of image‐guided prostate radiation therapy using AlignRT 9 , 10 these studies have primarily used EPID imaging for comparison, with emphasis placed on bony anatomy registration. Our study differs significantly from these studies in that we were able to exploit the superior image contrast of fan‐beam CT to allow for direct and accurate registration of the targeted soft tissue anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of the AlignRT system are its provision of real‐time tracking of patient surface location by monitoring of a region of interest during radiation therapy, its noninvasive imaging methodology, and its delivery of no extra radiation dose. It has been reported by multiple studies 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 that AlignRT can be an effective image guidance method for certain sites of radiation therapy treatment, including breast, intracranial stereotactic radiosurgery, thorax, and prostate.…”
Section: Introductionmentioning
confidence: 99%